Translation-mediated bilingual publishing as a development strategy: A content analysis of the language policies of peripheral scholarly journals - Li, Xiangdong (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
Local-language journals that include topics of regional interest and are published by regional institutions in the non-Anglophone world (peripheral journals, also called Global South journals in Development Studies) are underrepresented in major indexes and are struggling due to a lack of contributors, reviewers and financial support. Some have resorted to translation-mediated bilingual publishing as a development strategy to maintain their identity and increase their visibility and impact. To date, this strategy has received scant attention in the literature. The current research aims to explore why peripheral journals resort to the strategy and the ways in which it is put into practice. The overviews, instructions to authors and bilingually presented articles of 68 social science and humanities journals were reviewed through content analysis. The results suggest that the journals implement the strategy out of pragmatic and ideological concerns. It seems that the current use of translation as a development strategy is still an improvized mechanism instead of a standard model. Although many follow a similar pattern in some respects, there is a lack of management in the translation process and no agreed norms on cost coverage, translation strategy and presentation formats. This points to the necessity of further effort being expended to optimize the strategy in the future.